The Hot Limit of Solar-like Oscillations From Kepler Photometry - Balona, Luis A. (Frontiers in Astronomy and Space Sciences, 2020)
Kepler short-cadence photometry of 2347 stars with effective temperatures in the range 6000 – 10000 K was used to search for the presence of solar-like oscillations. The aim is to establish the location of the hot end of the stochastic convective excitation mechanism and to what extent it may overlap the δ Scuti/γ Doradus instability region. A simple but effective autocorrelation method is described which is capable of detecting low-amplitude solar-like oscillations, but with significant risk of a false detection. The location of the frequency of maximum oscillation power, ν max , and the large frequency separation, ∆ν, is determined for 167 stars hotter than 6000 K, of which 70 are new detections. Results indicate that the hot edge of excitation of solar-like oscillations does not appear to extend into the δ Scuti/γ Doradus instability strip.